الافاق و المقومات الرئيسة لآليات انشاء أسواق الأوراق المالية - حسن صبحي العباس (PROSPECTIVE RESEARCHES, 2023)
t Financial markets are the essential structure of any financial system anywhere. They help in a way or another in developing the national economy. The present research is an attempt to find the approaches to establish the general frame of any financial market concentration an the developing countries which try to copy with rapid growth of the world markets under the effects of changes and globalization. The researcher tries to find out some conclusion inside the framework of developing the financial markets, providing the securities to deal with them, and reforming currency to keep its value.